1996
DOI: 10.1182/blood.v88.10.4045.bloodjournal88104045
|View full text |Cite
|
Sign up to set email alerts
|

A combination of the effects of rare genotypes at the XK and KEL blood group loci results in absence of Kell system antigens from the red blood cells

Abstract: The 22 antigens of the Kell blood group system are located on a red blood cell (RBC) membrane glycoprotein that shows sequence homology with a family of metalloendopeptidases. Expression of the Kell system antigens is partially governed by XK, an X-linked gene that encodes the Kx protein; absence of Kx results in reduced Kell antigen expression. Almost total absence of Kell antigens from the RBCs of a German man with no symptoms of neuroacanthocytosis could not be due to the Kell- null phenotype, Ko, because h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…17 The vast majority of disease-causing XK mutations, however, comprised deletions, nonsense, or splice-site mutations predicting absent or truncated XK protein devoid of the Kell protein binding site. 3,4,9,[15][16][17][30][31][32] RBC protein Western blotting demonstrated absent RBC membrane-bound XK protein and XK/Kell complex. However, the wild-type XK-Western blot was not very strong under reducing conditions, most probably because reduced XK aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…17 The vast majority of disease-causing XK mutations, however, comprised deletions, nonsense, or splice-site mutations predicting absent or truncated XK protein devoid of the Kell protein binding site. 3,4,9,[15][16][17][30][31][32] RBC protein Western blotting demonstrated absent RBC membrane-bound XK protein and XK/Kell complex. However, the wild-type XK-Western blot was not very strong under reducing conditions, most probably because reduced XK aggregates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, depression of most Kell antigens can occur in some KEL3,-4 individuals but is most noticeable in KEL3,-4/Ko heterogygotes [12]. Recently it has been shown that a person with the KEL3 allele expressed almost no Kell antigens and this severe depression was due to a point mutation in a splice consensus sequence of XK, which would lead to absence of XK on the red cell membrane (McLeod phenotype) [43].…”
Section: Molecular Basis Of Kell Blood Group Phenotypesmentioning
confidence: 99%
“…5,46 In one case, the mutation occurs in an intron, five nucleotides downstream from the splice site, resulting in alternative splicing and a low level of normal splicing. 33,47 In this case, although a reduced level of normal XK is expected to be produced, Kx antigen was not detected on RBCs. Table 2).…”
Section: Single Nucleotide Mutations In the Coding Regionmentioning
confidence: 67%